A Practioner's Guide to Peer Counselling - de Rosenroll, David (Canadian Journal of Counselling and Psychotherapy, 2011)
This paper focuses on key peer counselling implementation and research questions. Included are issues as to whether or not peer counselling expands professional support services; the environmental impact, training content, process and duration of peer counselling programs, selection of peer counsellors; referral patterns; and types of clients and problems undertaken. The author draws from qualitative research methodologies, such as participant observation and phenomenology, which are more readily associated with the social sciences and education to suggest a variety of ways of collecting data which will help us to respond to the research questions and to remain sensitive to our program goals and contextual limitations.